2016
DOI: 10.1007/s40119-016-0058-2
|View full text |Cite
|
Sign up to set email alerts
|

Edoxaban: A Comprehensive Review of the Pharmacology and Clinical Data for the Management of Atrial Fibrillation and Venous Thromboembolism

Abstract: Historically, vitamin K antagonists have been the only class of oral anticoagulants available. Despite our experience with warfarin over the past 60 years, its use is associated with several pharmacokinetic and clinical disadvantages including unpredictable dosing, frequent monitoring, and delayed onset and offset. Edoxaban, an oral direct Xa inhibitor, may provide clinicians with an additional option in patients requiring chronic anticoagulation. This review examines the pharmacology and clinical data of edox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 41 publications
1
72
0
Order By: Relevance
“…FXa combined with FVa stimulates prothrombin into thrombin which activates fibrinogen and finally forms fibrin. 24 Thus increased FXa contributes to more fibrin leading to rapid clotting formation and thus the coagulation time shortens. Therefore platelets after chemotherapy may contribute to the reduced clotting time and increased TAT of NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…FXa combined with FVa stimulates prothrombin into thrombin which activates fibrinogen and finally forms fibrin. 24 Thus increased FXa contributes to more fibrin leading to rapid clotting formation and thus the coagulation time shortens. Therefore platelets after chemotherapy may contribute to the reduced clotting time and increased TAT of NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 50% of the drug is excreted renally. It has a half-life of 10-14 hours [15,19,28] (see Table 1).…”
Section: Admementioning
confidence: 99%
“…Edoxaban is approved both for SSE prevention in patients with non-valvular AF and VTE treatment. In the Edoxaban versus Warfarin in Patients with Atrial Fibrillation (ENGAGE AF-TIMI 48) trial, edoxaban has shown to be non-inferior to warfarin for SSE prevention [28] (see Table 2). However, a separate analysis that was published shows that at CrCl of >95 ml/min, edoxaban is not as protective as warfarin against SSE.…”
Section: Clinical Usementioning
confidence: 99%
See 2 more Smart Citations